Childfree Dalam Perspektif Islam Dan Sosial, Dan Implikasinya Terhadap Ketahanan Keluarga - Alfa Syahriar; Zahrotun Nafisah; Dhania Murni Safitri; Muhammad Ichsan Nur Hanif (Isti`dal : Jurnal Studi Hukum Islam, 2023)
This research is intended to examine the effectiveness of childfree from an Islamic and social perspective, then examine its implications for family resilience, when childfree becomes the choice of husband and wife in building a household. The study of childfree in Islam needs to be carried out with the consideration that the majority of Indonesia's population is Muslim, so that childfree conflicts with Islamic teachings in the form of marriage, which in essence is to produce offspring. Likewise, in the social realm, there has been a paradigm of society since ancient times, more children, more good fortune, so that it becomes a general understanding that the measure of a family's welfare is heredity, in fact the more offspring the more prosperous it will be. Therefore, this research was conducted using a qualitative approach with the literature study method. In the context of Islamic law, researchers use the maqasid al-shariah theory, while in the social context, they use the theory of structural functionalism. Data analysis in this study used the Miles and Hubberman analysis technique. The results of this study: 1) the basic law of childfree is mubah (permissible), it's just that it doesn't meet the ideal values for a family. 2) Socially, the consequence of childfree is the shallowing of family functions, which has an impact on social functions in society. 3) In the dimensions of the legality of family integrity and social psychology, it can be seen that childfree can affect family resilience.